Japan's economic dilemma : the institutional origin of prosperity and stagnation - Gao, Bai, 1955- (Cambridge University Press, 2001)
Bai Gao's analysis of Japan's economic story goes beyond other analyses to demonstrate how the same economic institutions could produce stunning economic success and the slump of the 1990s. Those who have been following the lively debate over 'What became of the Japanese miracle?' will be rewarded by Gao's contribution.